(Inter)Cultural Dialogue and Identity in Lithuanian Literature - Ragaišienė, Irena,Rundholz, Adelheid,Aurylaitė, Kristina,Višomirskytė, Vijolė,Eidukvičienė, Rūta,Žindžiuvienė, Ingrida Eglė,Danytė, Milda Julija,Kuizinienė, Dalia,Leonavičienė, Aurelija,Macijauskaitė-Bonda, Jurgita,Dugo, Carmen Caro,Barniškienė, Sigita,Cummings, Elizabeth Mary (V&R unipress, 2023)
This book illustrates that the idea of a ‘national’ literature is profoundly problematic. Chapters on boundaries and crisscrossing show how a nation and its writers’ works do not exist in isolation from their history. Stressing migration and (inter)cultural dialogue, authors explore how the characters in the texts establish a sense of belonging both within the context of migrations and within the context of Lithuania since its independence. The final series of essays in this book discusses Lithuanian literature abroad that is in translation. Angaben zur beteiligten Person Ragaišienė: Irena Ragaišienė, Ph.D., teaches at Vytautas Magnus University, Kaunas, Lithuania. Her recent publications are on identity and displacement in literature of migration. Angaben zur beteiligten Person Rundholz: Adelheid Rundholz, Ph.D., teaches at Johnson C. Smith University in Charlotte, NC, USA. Her research interests are literature of migration, literary theory, world literature, and translation.
9783737016155
Keywords: Aufsatzsammlung; Intercultural dialogue; Literature of migration; National identity; Lithuanian literature; Contemporary Lithuanian literature